COVID-19 Assessment and Testing in Rural Communities During the Pandemic: Cross-sectional Analysis - Jonathan Fitzsimon; Oliver Gervais; Chelsea Lanos (JMIR Publications, 2022)
BackgroundThe COVID-19 pandemic exacerbated the need for urgent improvements in access to health care for rural, remote, and underserviced communities. The Renfrew County Virtual Triage and Assessment Centre (VTAC) was designed to provide access to COVID-19 testing and assessment with a family physician. The goal was to protect emergency departments and 911 paramedics while ensuring that nobody was left at home, suffering in silence. Residents were encouraged to call their own family physician for any urgent health needs. If they did not have a family physician or could not access their usual primary care provider, then they could call VTAC. This study reports on the output of a service model offering access to assessment and COVID-19 testing through a blend of virtual and in-person care options by a multidisciplinary team. ObjectiveThe purpose of this study was to assess the ability of VTAC to provide access to COVID-19 assessment and testing across rural, remote, and underserviced communities. MethodsWe conducted a cross-sectional analysis of the data derived from the cases handled by VTAC between March 27, 2020 (launch day), and September 30, 2020. ResultsResidents from all 19 census subdivisions and municipalities of Renfrew County accessed VTAC. A total of 10,086 family physician assessments were completed (average 64 per day). Of these, 8535 (84.6%) assessments were to unique patient users. Thirty physicians provided care. Using digital equipment setup in the patients' home, 31 patients were monitored remotely. VTAC community paramedics completed 14,378 COVID-19 tests and 3875 home visits. ConclusionsRenfrew County's experience suggests that there is tremendous synergy between family physicians and community paramedics in providing access to COVID-19 assessment and COVID-19 testing. The blended model of virtual and in-person care is well suited to provide improved access to other aspects of health care post pandemic, particularly for patients without a family physician.